Business plan of juntta 2.0- crowdfunding platform for Millennium BCP - Gomes, Mafalda Estêvão (2020)
This thesis is a Business Plan of a Peer-to-Peer lending platform, Juntta 2.0, designed for Millennium BCP, to understand the economic viability of entering in this market. The similarities between the type of business of Peer-to-Peer and BCP business activities, makes Peer-to-Peer lending platform the best type of crowdfunding platform for BCP. In Portugal, the crowdfunding market is under-exploit, without many players, yet, which creates comparative advantages, as the new product is more competitive, when comparing to traditional ones. At the same time, it allows Millennium to be prepared to face the new and stronger competition on the market. As a new and risky business, it might have some reluctance from the crowd. After all the considerations, the platform is a value added for the bank, due to its positive Net Present Value (NPV), considering a 5 years’ horizon on estimations.